Promoting Pre-service Teachers’ Critical Intercultural Awareness using Problem-based learning - Ratna Andhika Mahaputri; Misdi Misdi; Fazri Nur Yusuf; Azlina Abdul Aziz (Yayasan Keluarga Guru Mandiri, 2024)
Promoting ICC has been discussed widely in the EFL context as one of the goals of foreign language learning. The present study explores implementing online problem-based learning (PBL) in an EFL classroom to promote critical intercultural awareness (CIA) in a teacher education context. The participants were 40 pre-service teachers who enrolled in Intercultural communication subjects for the semester. Drawing upon the PBL approach in teaching intercultural communication, the study deployed action research (AR) where participants engaged in the four phases: planning, acting, observing, and evaluating. Data were gathered through a series of guided observations and a written interview. The findings showed that the learners' capacity to be aware of cultural differences can be promoted by incorporating problem-based learning. In this sense, the learners develop their critical thinking regarding encountering a wide range of cultural diversity to promote CIA. In addition, PBL successfully enables pre-service teachers to be critically aware of intercultural issues and make meaningful reflections on their own culture and other people's cultures. This study contributes to teacher education by preparing EFL teachers to develop one of the aspects of Intercultural Competence.